(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2021)
This paper analyzes the conflict that arose in the notary’s office of the Catalan village of La Bisbal d’Empordà during the first half of the 14th century, due to the high rates demanded by the local notaries. For this reason, in 1321the bishop of Girona, master of the notary’s office, ordered an appraisal of prices. The examination of this episcopal document allows a detailed study of the tariff to be charged for each notarial instrument. In addition, the comparative study with other appraisals preserved for the same area reveals a certain circulation of this type of tariff relations throughout the territory.